A wastewater treatment method based on carbonized nitrogen modified CN-CPBA catalyst
The CN-CPBA catalyst was prepared by covalently modified graphite phase nitrogen carbide (CN) catalyst combined with 4-carboxyphenylboric acid (CPBA), which solved the shortcomings of CN catalyst in the photocatalytic self-Fenton system and achieved efficient water treatment effect.
Patent Information
- Application Number
- CN202310063121.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-16
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-01-16
AI Technical Summary
The existing photocatalyst graphite phase nitrogen carbide (CN) has problems with low charge carrier mobility, small specific surface area, and low photoenergy utilization, which is difficult to meet the construction needs of photocatalytic self-Fenton system.
By integrating organic motifs by covalent bonding, conjugated organic chemical monomers are introduced into the graphite plane of CN, their band structure and electron migration characteristics are adjusted, and 4-carboxyphenylboric acid (CPBA) is combined with CN by hydrothermal method to prepare a CN-CPBA modified photo-Fenton catalyst.
The photocatalytic activity is improved, the specific surface area of the catalyst is increased, the separation of photogenerated electrons and holes is promoted, the generation of hydrogen peroxide and the degradation efficiency of organic pollutants is improved, and the effect of water treatment is significantly improved.
Smart Images

Figure CN116037204B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a carbonized nitrogen modified CN-CPBA catalyst and application thereof in water treatment, belonging to the technical field of environmental material preparation. Background Art
[0002] With the development of human life, water pollution has become more and more serious. In these polluted water sources, there are a large number of phenolic compounds with strong carcinogenicity, which pose a great threat to organisms. These compounds are difficult to degrade naturally and need to be treated before they can be removed.
[0003] Fenton technology has been proven to be effective in removing organic pollutants in water that cannot be naturally degraded due to its strong oxidation ability. However, its application is limited by the fact that the consumed hydrogen peroxide needs to be continuously replenished, and the Fe ions cannot be circulated well, which will produce new pollution such as iron sludge. The Fenton-like technology based on the Fenton technology has solved the defect that Fe ions cannot be circulated to a certain extent, but it still requires continuous addition of hydrogen peroxide. Therefore, the in-situ efficient generation of hydrogen peroxide and activation in pollutants has become a problem to solve the relationship between these technologies. Therefore, the in-situ generation of H 2 O 2 Photocatalysis has attracted people's attention since the Fenton technology. It is achieved by generating H in situ under light irradiation through photocatalysts. 2 O 2 , and then combined with Fenton reagent to construct the Fenton cycle for the degradation of pollutants.
[0004] Among many photocatalysts, graphite carbonized nitrogen (CN) is widely used in the field of photocatalysis because of its suitable energy band structure, certain light response ability, good stability and easy modification. Graphite carbonized nitrogen (CN) is a metal-free organic polymer semiconductor. It not only has a large π conjugated structure and a suitable energy band, but also has excellent chemical / physical stability and a simple preparation process. It shows excellent photocatalytic performance and is widely used in the production of hydrogen peroxide and the degradation of various pollutants. However, the original graphite carbonized nitrogen (CN) has many defects, such as low charge carrier mobility, small specific surface area, and low light energy utilization. Therefore, it is the key to solve the problem to modify it appropriately so that it meets the requirements of the construction of the photocatalytic self-Fenton system. In the prior art, the modification methods of carbonized nitrogen (CN) generally include morphology control, element doping, composite with other semiconductor materials, copolymerization with other molecules, and introduction of template agents.
[0005] Therefore, it is necessary to develop a new method to modify carbonized nitrogen (CN) catalysts to make them suitable for the construction of photocatalytic self-Fenton system. Summary of the invention
[0006] In view of the technical defects existing in the prior art, the present invention integrates organic motifs through covalent bonds and introduces conjugated organic chemical monomers into the graphite plane of CN to adjust its energy band structure and electron migration characteristics, thereby improving its photocatalytic activity. 4-Carboxyphenylboronic acid (CPBA) is combined with CN by a hydrothermal method to prepare a CN-CPBA modified photo-Fenton catalyst.
[0007] In order to achieve the above purpose, the specific scheme of the present invention is as follows:
[0008] The first object of the present invention is to provide a method for preparing a carbonized nitrogen modified catalyst CN-CPBA, characterized in that it comprises the following steps:
[0009] S1: Preparation of graphite phase carbon nitride (CN) as a photoactive substrate material: melamine is ground and dispersed and placed in a crucible with a lid, which is then calcined in a muffle furnace. After cooling, it is washed, filtered, dried, ground and dispersed to obtain CN;
[0010] S2: Preparation of catalyst CN-CPBA: 4-carboxyphenylboronic acid (CPBA) was dissolved in a mixture of ethanol and water, CN was added, and after uniform dispersion, it was transferred to a hydrothermal kettle for hydrothermal reaction. After cooling, it was washed and dried to obtain the CN-CPBA catalyst.
[0011] In one embodiment of the present invention, the calcination temperature in step S1 is 520-580°C;
[0012] In one embodiment of the present invention, the calcination time in step S1 is 3-5h;
[0013] In one embodiment of the present invention, the mass ratio of carbonized nitrogen to 4-carboxyphenylboronic acid in step S2 is 1:1.1-1:1.6;
[0014] In one embodiment of the present invention, in step S1, the drying temperature is 50-80°C;
[0015] In one embodiment of the present invention, in step S1, the drying time is 8-12 hours;
[0016] In one embodiment of the present invention, in step S2, the drying temperature is 50-80°C;
[0017] In one embodiment of the present invention, in step S2, the drying time is 8-12 hours;
[0018] In one embodiment of the present invention, the volume ratio of ethanol to water in step S2 is 1:4-1:1.
[0019] In one embodiment of the present invention, the temperature of the hydrothermal reaction in step S2 is 120-180° C., and the reaction time is 6-10 h.
[0020] The second object of the present invention is to provide a carbonized nitrogen modified catalyst CN-CPBA.
[0021] The third object of the present invention is to provide a photocatalytic self-Fenton water treatment method using a CN-CPBA catalyst; comprising the following steps:
[0022] The specific steps are: add CN-CPBA catalyst to the wastewater to be treated, stir at high speed to reach the adsorption-desorption equilibrium on the catalyst surface, and then add Fe 2+ A photocatalytic self-Fenton system is constructed as a Fenton reagent, and then it is placed under a light source for irradiation. Oxygen is continuously passed during the reaction to keep the solution saturated with oxygen.
[0023] In one embodiment of the present invention, the stirring method is mechanical stirring.
[0024] In one embodiment of the present invention, Fe 2+ The mass ratio to the CN-CPBA catalyst is 1:20-1:5.
[0025] In one embodiment of the present invention, the oxygen supply method is selected from directly supplying oxygen or supplying air;
[0026] In one embodiment of the present invention, the wavelength of the light source is in the range of 200 to 1300 nm.
[0027] In one embodiment of the present invention, the light source is sunlight;
[0028] In one embodiment of the present invention, the light source is an artificial light source, such as a xenon lamp, an ultraviolet lamp, a high-pressure mercury lamp, an LED lamp, a laser, and the like.
[0029] In one embodiment of the present invention, it is used to degrade one or more of 4-chlorophenol, 2,4-dichlorophenol, bisphenol A, tetracycline, hydroquinone, resorcinol, and ciprofloxacin.
[0030] Beneficial effects of the present invention:
[0031] (1) 4-Carboxyphenylboronic acid was loaded onto carbonized nitrogen by covalent modification to obtain the photocatalyst CN-CPBA that can be used for photocatalytic self-Fenton reaction, achieving efficient mineralization of phenolic organic pollutants. The modified catalyst obtained has a lower recombination rate of photogenerated carriers, so that more photogenerated electrons are used for the production of hydrogen peroxide and the valence cycle of Fe ions in the Fenton system, thereby promoting the generation of more ·OH, and coordinating the hole end of the catalyst itself to degrade mineralized pollutants, achieving water purification.
[0032] (2) CN was used as the photocatalytic substrate material, and the mass of the precursor CPBA added during the hydrothermal process was adjusted to obtain photocatalytic H production. 2 O 2 The modified CN-CPBA nanosheets with the best efficiency can effectively increase the active specific surface area of the catalyst, stimulate and effectively separate photogenerated electrons and holes, and promote the process of reducing oxygen to generate hydrogen peroxide and degradation. Under simulated sunlight, the best sample produced 156.4 μmol g in pure water in 1 hour. -1 H 2 O 2 .
[0033] (3) The water treatment method based on CN-CPBA of the present invention has significant activity advantages. Under simulated sunlight, the degradation rate of 20ppm 4-chlorophenol (4-CP) solution reaches 99.8% within 1 hour, and the kinetic k value is 11.7 times that of the original CN, which has efficient catalytic degradation performance; at the same time, the TOC removal rate of the photo-Fenton process in 1 hour is 74.5%, which is 4.4 times that of the original CN, that is, it has the characteristics of efficient mineralization of organic pollutants. In addition to having excellent degradation activity, the catalyst has good stability and can be used for multiple water treatments. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 FTIR spectra of CN-CPBA prepared in Example 2 and catalyst CN prepared in Comparative Example 1.
[0035] Figure 2 (a) TEM image of CN-CPBA prepared in Example 2 (scale is 100 nm), (b) SEM image of CN-CPBA (scale is 5 μm), and (c~f) EDX mapping images of CN-CPBA.
[0036] Figure 3 High-resolution XPS spectra of (a) C 1s, (b) N 1s, (c) O 1s and (d) B1s of CN-CPBA prepared in Example 2.
[0037] Figure 4 This is a graph showing the yield of hydrogen peroxide from the CN-CPBA catalyst photocatalyst prepared in Examples 1-6.
[0038] Figure 5 The degradation activity correlation diagram of the prepared samples, wherein a is the degradation curve diagram of the samples prepared in Examples 1-6 and Comparative Example 1, and b is the degradation curve diagram of the samples prepared in different FeCl 2 ·4H 2O added amount of photocatalytic self-Fenton degradation curve, c is the photocatalytic degradation of CN prepared in Example 1, the photocatalytic degradation of CN-CPBA prepared in Example 2 and the k value bar graph of the photocatalytic degradation of CN prepared in Example 1, the photocatalytic degradation of CN-CPBA prepared in Example 2, the photocatalytic self-Fenton degradation of CN-CPBA prepared in Example 3 and the TOC removal rate bar graph, d is the photocatalytic self-Fenton cycle performance diagram of CN-CPBA prepared in Example 2. DETAILED DESCRIPTION
[0039] The present invention will be further described below in conjunction with specific implementation examples.
[0040] The catalyst prepared in the present invention is evaluated for its photo-self-Fenton catalytic performance: the photo-self-Fenton catalytic performance of the system is mainly evaluated by dispersing the catalyst in a 4-chlorophenol (4-CP) solution, and then evaluating the degradation, total organic carbon removal rate and the residual amount of self-produced hydrogen peroxide under light. In a typical degradation reaction, 20 mg of the catalyst is added to 20 mL of a 4-chlorophenol (20 ppm) aqueous solution, and stirred at high speed for 30 min to reach the adsorption-desorption equilibrium on the catalyst surface. It is then placed under stable light for reaction, and a balloon filled with pure oxygen is used to bubble into the reactor during the reaction to keep the solution saturated with oxygen. 1 mL of the solution is drawn at regular intervals, and the catalyst powder is removed with a 0.45 μm 13 mm nylon syringe filter for liquid phase testing, and then its concentration is tested by liquid chromatography; the degradation performance is indexed by the rate constant k value.
[0041] The concentration of organic pollutants in the solution was automatically analyzed and detected by ultra-high performance liquid chromatography (HPLC) equipped with a Venusil HILIC carbon 18 liquid column (4.6×250 mm, 5 μm). The mobile phase used was chromatographic grade methanol / ultrapure water (v / v) = 70 / 30, and the flow rate was 1.00 mL min -1 The obtained spectrum has a retention time of about 6 minutes, which is the peak position corresponding to 4-CP. After peak area integration, the ratio of the initial 4-CP solution to the unreacted solution is the degree of catalytic degradation. The degradation intermediates of 4-CP are determined by ultra-high performance liquid chromatography-tandem quadrupole time-of-flight mass spectrometry. The total organic carbon (TOC) removal rate of the solution is determined by a total organic carbon analyzer and calculated by formula (1), where c 1 TOC removal at 1 hour, c 0 is the initial solution TOC: TOC removal rate (%) = 1-c 1 / c 0 (1)
[0042] The photocatalytic hydrogen peroxide production test was carried out as follows. Prepare 0.018 mol·L -1 Potassium titanium oxalate calibration solution containing 5 vol% concentrated sulfuric acid was used to make a standard curve. 3 mL was added to the above 2 mL filtered reaction solution. After shaking, wait for 10 minutes to allow the reaction solution and potassium titanium oxalate to react completely. An appropriate amount of solution was placed in a quartz cuvette. The corresponding absorbance was detected at a wavelength of 400 nm using a UV-visible spectrophotometer. The H was calculated by comparing the standard curve relationship. 2 O 2 concentration.
[0043] Example 1
[0044] (1) Preparation of CN photoactive substrate: 20 g of melamine was added to a covered crucible and heated in a muffle furnace at 2 °C min -1 The mixture was heated to 520°C at a heating rate of 100 °C and kept at this temperature for 3 h. After cooling to room temperature, the yellow block was ground into powder, washed with deionized water, filtered, and then dried in an oven at 50°C for 8 h to obtain CN.
[0045] (2) Preparation of modified catalyst CN-CPBA: The original carbonized nitrogen material was covalently modified by high-temperature hydrothermal method. CN and CPBA prepared in step (1) were added to a mixture of 10 ml ethanol and 40 ml water in a mass ratio of 1:1.1. Then, it was dispersed and stirred evenly by ultrasound, transferred to a hydrothermal kettle for hydrothermal reaction at a reaction temperature of 120°C for 6 hours, taken out after cooling, washed several times with ethanol and water, and then placed in a 50°C oven to dry for 8 hours to finally obtain CN-CPBA catalyst.
[0046] Example 2
[0047] (1) Preparation of CN photoactive substrate: 20 g of melamine was added to a covered crucible and heated in a muffle furnace at 3 °C min -1 The mixture was heated to 520°C at a heating rate of 100 °C and kept at this temperature for 4 h. After cooling to room temperature, the yellow block was ground into powder, washed with deionized water, filtered, and then dried in an oven at 60°C for 9 h to obtain CN.
[0048] (2) Preparation of modified catalyst CN-CPBA: The original carbonized nitrogen material was covalently modified by high-temperature hydrothermal method. CN and CPBA prepared in step (1) were added to a mixture of 10 ml ethanol and 40 ml water in a mass ratio of 1:1.2. Then, it was dispersed and stirred evenly by ultrasound, transferred to a hydrothermal kettle for hydrothermal reaction at a reaction temperature of 150°C for 8 hours. After cooling, it was taken out and washed several times with ethanol and water, and then placed in a 60°C oven for 9 hours to finally obtain the CN-CPBA catalyst.
[0049] Example 3
[0050] (1) Preparation of CN photoactive substrate: 20 g of melamine was added to a covered crucible and heated in a muffle furnace at 4 °C min -1 The mixture was heated to 530°C at a heating rate of 100 °C and kept at this temperature for 5 h. After cooling to room temperature, the yellow block was ground into powder, washed with deionized water, filtered, and then dried in an oven at 70°C for 10 h to obtain CN.
[0051] (2) Preparation of modified catalyst CN-CPBA: The original carbonized nitrogen material was covalently modified by high-temperature hydrothermal method. CN and CPBA prepared in step (1) were added to a mixture of 10 ml ethanol and 40 ml water in a mass ratio of 1:1.3. Then, it was dispersed and stirred evenly by ultrasound, transferred to a hydrothermal kettle for hydrothermal reaction at a reaction temperature of 160°C for 9 hours. After cooling, it was taken out and washed several times with ethanol and water, and then placed in a 70°C oven for 10 hours to finally obtain the CN-CPBA catalyst.
[0052] Example 4
[0053] (1) Preparation of CN photoactive substrate: 20 g of melamine was added to a covered crucible and heated in a muffle furnace at 5 °C min -1 The temperature was raised to 540°C at a rate of 100 °C and kept constant at this temperature for 4 h. After cooling to room temperature, the yellow block was ground into powder, washed with deionized water, filtered, and then dried in an oven at 80°C for 11 h to obtain CN.
[0054] (2) Preparation of modified catalyst CN-CPBA: The original carbonized nitrogen material was covalently modified by high-temperature hydrothermal method. CN and CPBA prepared in step (1) were added to a mixture of 10 ml ethanol and 40 ml water in a mass ratio of 1:1.4. Then, it was evenly dispersed and stirred by ultrasound, transferred to a hydrothermal kettle for hydrothermal reaction at a reaction temperature of 170°C for 10 hours. After cooling, it was taken out and washed several times with ethanol and water, and then placed in an oven at 80°C for 11 hours to finally obtain the CN-CPBA catalyst.
[0055] Example 5
[0056] (1) Preparation of CN photoactive substrate: 20 g of melamine was added to a covered crucible and heated in a muffle furnace at 6 °C min -1 The temperature was raised to 550°C at a rate of 100 °C and kept constant at this temperature for 4 h. After cooling to room temperature, the yellow block was ground into powder, washed with deionized water, filtered, and then dried in an oven at 80°C for 12 h to obtain CN.
[0057] (2) Preparation of modified catalyst CN-CPBA: The original carbonized nitrogen material was covalently modified by high-temperature hydrothermal method. CN and CPBA prepared in step (1) were added to a mixture of 10 ml ethanol and 40 ml water in a mass ratio of 1:1.5. Then, it was evenly dispersed and stirred by ultrasound, transferred to a hydrothermal kettle for hydrothermal reaction at a temperature of 180°C for 9 hours, and then taken out after cooling, washed several times with ethanol and water, and then placed in an oven at 80°C for 12 hours to finally obtain the CN-CPBA catalyst.
[0058] Example 6
[0059] (1) Preparation of CN photoactive substrate: 20 g of melamine was added to a covered crucible and heated in a muffle furnace at 10 °C min -1 The temperature was raised to 560°C at a rate of 100 °C and kept constant at this temperature for 4 h. After cooling to room temperature, the yellow block was ground into powder, washed with deionized water, filtered, and then dried in an oven at 80°C for 12 h to obtain CN.
[0060] (2) Preparation of modified catalyst CN-CPBA: The original carbonized nitrogen material was covalently modified by high-temperature hydrothermal method. CN and CPBA prepared in step (1) were added to a mixture of 10 ml ethanol and 40 ml water in a mass ratio of 1:1.6. Then, it was evenly dispersed and stirred by ultrasound, and transferred to a hydrothermal kettle for hydrothermal reaction at a reaction temperature of 180°C for 10 hours. After cooling, it was taken out and washed several times with ethanol and water, and then placed in an oven at 80°C for 12 hours to finally obtain the CN-CPBA catalyst.
[0061] Example 7
[0062] Different Fe 2+ Effect of addition amount on photocatalytic degradation activity of self-Fenton system:
[0063] (1) 20 mg of CN-CPBA prepared in Example 2 was added to 20 mL of 4-CP solution (20 ppm), and then placed on a stirring table and stirred for 30 min.
[0064] (2) Add 2 mg, 5 mg, and 10 mg of FeCl to the above solution respectively. 2 ·4H 2 O initiated the self-Fenton reaction, and oxygen was continuously supplied during the process. Every 10 min, 1 mL of liquid was taken and passed through a 0.45 μm 13 mm nylon syringe filter, and then its concentration was tested by liquid chromatography.
[0065] Comparative Example 1
[0066] (1) Preparation of CN photoactive substrate: 20 g of melamine was added to a covered crucible and heated in a muffle furnace at 2.3 °C min -1 The temperature was raised to 550°C at a rate of 100 °C and kept constant at this temperature for 4 h. After cooling to room temperature, the yellow block was ground into powder, washed with deionized water, filtered, dried, ground and dispersed to obtain CN.
[0067] Comparative Example 2
[0068] Fenton system degradation activity:
[0069] (1) 10.3 μmol of H 2 O 2 Add into 20 mL 4-CP solution (20 ppm), and then place on a stirring table and continue stirring for 30 min.
[0070] (2) Add 5 mg FeCl to the above solution. 2 ·4H 2 O triggered the Fenton reaction, and 1 mL of the liquid was taken every 10 min to pass through a 0.45 μm 13 mm nylon syringe filter, and then its concentration was tested by liquid chromatography.
[0071] The degradation activity, H 2 O 2 concentration, TOC removal rate.
[0072] Take 20 mg of the photocatalyst CN obtained in Comparative Example 1 and 20 mg of CN-CPBA obtained in Example 2 and add them to 20 mL of 4-CP (20 ppm) aqueous solution, and stir at high speed for 30 minutes to reach the adsorption-desorption equilibrium on the catalyst surface. Then place it under simulated sunlight (300W Xe) for reaction. Oxygen is continuously passed through the reaction process to maintain oxygen saturation. 1 mL of solution is drawn every 10 minutes, and the catalyst powder is removed with a 0.45μm 13mm nylon syringe filter for liquid phase testing. After 60 minutes of reaction, the photocatalyst CN and CN-CPBA can degrade 52% and 87% of 4-CP, respectively, and the average degradation kinetic k values are 0.008min, respectively. -1 and 0.032min -1 ;
[0073] Take 20 mg of CN-CPBA obtained in Example 2 and add it to 20 mL of 4-CP (20 ppm) aqueous solution, and stir at high speed for 30 min to reach the adsorption-desorption equilibrium on the catalyst surface. Then place it under simulated sunlight (300W Xe) for reaction, and continue to pass oxygen during the reaction to maintain oxygen saturation. After 1 h of reaction, take 1 mL of solution, remove the catalyst powder with a 0.45 μm 13 mm nylon syringe filter, and then test the TOC with a total organic carbon analyzer. For the homogeneous photocatalytic self-Fenton experiment, add FeCl 2 ·4H 2 The amount of O was 5 mg. The final homogeneous Fenton TOC removal rate was 74.5%, and the average degradation kinetic k value was 0.099 min -1 , while the photocatalytic CN-CPBA system did not add FeCl 2 ·4H 2 O, only 36% after 1 hour of simulated sunlight irradiation, which illustrates the advantage of the photo-Fenton system in mineralizing refractory organic matter.
[0074] The catalyst without hydrothermal modification had almost no activity improvement, and the H 2 O 2 The concentration is almost undetectable.
[0075] It can be seen that CPBA modification of CN is necessary for the subsequent Fenton synergy of the catalyst, making CN produce H 2 O 2 And degradation performance are improved accordingly.
[0076] Test data analysis:
[0077] Figure 1 The Fourier transform infrared spectroscopy (FTIR) in the figure shows that CN-CPBA has a higher concentration of 3076 and 1627 cm-1 compared with CN. -1 There is an obvious prominent peak at , indicating that CPBA and CN are not simply physically mixed, but connected through amide bonds.
[0078] Figure 2 Transmission electron microscopy (TEM) in the Figure 3 shows that CN-CPBA presents stacked lamellae, similar to ordinary CN, and EDX shows that the elements are uniformly dispersed on the catalyst surface.
[0079] Figure 3X-ray photoelectron spectroscopy (XPS) further explored the fine chemical bond between CN-CPBA and CN. A new O=CN peak appeared at 287.5eV in C1s, which was significantly enhanced in combination with the C=O / CO peak at 531.6eV in O1s. Finally, a very obvious new peak OBC appeared in B1s, all of which indicated that CPBA and CN were connected by amide bonds.
[0080] Figure 4 It can be seen that the H 2 O 2 The yield is 2.93 times that of CN prepared in Example 1, which will be beneficial to the subsequent photocatalytic self-Fenton to produce more ·OH for pollutant degradation. This also shows that CPBA-modified CN-CPBA catalyst can effectively improve H 2 O 2 Yield.
[0081] Figure 5 As can be seen from Figure a, at the optimal CPBA modification ratio, the degradation activity of the CN-CPBA prepared in Example 2 is improved from 52% to 87% within 1 hour compared with the CN prepared in Comparative Example 1; Figure b shows that after constructing the photocatalytic self-Fenton, the degradation activity of the CN-CPBA prepared in Example 2 is further improved to 99% degradation within 60 minutes; Figure c shows that the k value of the CN-CPBA photocatalytic self-Fenton system prepared in Example 2 is improved by 11.7 times compared with the CN prepared in Comparative Example 1, and the TOC removal rate is improved by 4.4 times; and in comparison with the Fenton system, when H 2 O 2 When the amount added is twice the amount produced in situ in the photocatalytic self-Fenton system, the Fenton process has only a 28.2% TOC removal rate, proving the superiority of the photocatalytic self-Fenton system water treatment method. From Figure d, it can be seen that even after 4 cycles, the activity of the catalyst has not decreased significantly, proving that the CN-CPBA catalyst has good stability.
[0082] In summary, the present invention interacts the organic small molecules with the CN main body through strong covalent bonds, which is different from the electrostatic link of physical mixing, and can provide an effective electron transfer channel, thereby adjusting its electronic and energy band structure and improving its photocatalytic activity. The light-excited carrier separation and migration on the CN-CPBA catalyst promotes the surface oxygen reduction H 2 O 2 The production of Fe 2+ Consumes H generated in situ 2 O 2 , thereby achieving a self-Fenton cycle and promoting the production of highly oxidizing ·OH. Other active oxygen radicals generated during the reaction, such as ·O2- This synergistic effect with the photoexcited holes transferred to the surface leads to efficient water treatment of organic pollutants.
[0083] 4-Carboxylphenylboronic acid was loaded onto carbonized nitrogen by covalent modification to obtain the modified carbonized nitrogen photocatalyst CN-CPBA. The catalyst has a lower recombination rate of photogenerated carriers, so that more photogenerated electrons are used for the production of hydrogen peroxide and the valence cycle of Fe ions in the Fenton system, thereby promoting the generation of more ·OH and cooperating with the hole end of the catalyst itself to achieve efficient mineralization of phenolic organic pollutants. CN was used as the photocatalytic substrate material, and the mass of the precursor CPBA added during the hydrothermal process was adjusted to obtain the photocatalytic H production. 2 O 2 The modified CN-CPBA nanosheets with the best efficiency can effectively increase the active specific surface area of the catalyst, stimulate and effectively separate photogenerated electrons and holes, and promote the process of reducing oxygen to generate hydrogen peroxide and degradation. Under simulated sunlight, the best sample produced 156.4 μmol g in pure water in 1 hour. -1 H 2 O 2 Under simulated sunlight, the degradation rate of 20ppm 4-chlorophenol solution reached 99.8% within 1 hour, and the kinetic k value was 11.7 times that of the original CN, which has efficient catalytic degradation performance; at the same time, the TOC removal rate of the photo-self-Fenton process in 1 hour was 74.5%, which is 4.4 times that of the original CN, that is, it has the characteristics of efficient mineralization of organic pollutants; at the same time, the catalyst also has good stability and still maintains high activity after multiple cycles.
[0084] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the protection scope of the present invention.
Claims
1. A photocatalytic self-Fenton water treatment method, characterized in that: The specific steps are: add CN-CPBA catalyst to the wastewater to be treated, stir at high speed to reach the adsorption-desorption equilibrium on the catalyst surface, and then add Fe 2+ As a Fenton reagent, a photocatalytic self-Fenton system was constructed, and then it was placed under a light source for irradiation. During the reaction, oxygen was continuously supplied to keep the solution saturated with oxygen. H2O2 was generated by the reduction of photogenerated electrons from CN-CPBA, and then reacted with Fe 2+ Synergistically trigger the Fenton reaction to produce hydroxyl radicals and achieve efficient mineralization of organic pollutants; The preparation method of the CN-CPBA catalyst comprises the following steps: S1: Preparation of carbonized nitrogen as a photoactive substrate material: Melamine is ground and dispersed and placed in a crucible with a lid, which is then calcined in a muffle furnace. After cooling, it is washed, filtered, dried, ground and dispersed to obtain CN; S2: Preparation of catalyst CN-CPBA: 4-carboxyphenylboric acid was dissolved in a mixture of ethanol and water, CN was added, and the mixture was evenly dispersed and transferred to a hydrothermal reactor for hydrothermal reaction. After cooling, the mixture was washed and dried to obtain the CN-CPBA catalyst; In step S1, the calcination temperature is 520-580°C and the calcination time is 3-5 h; The temperature of the hydrothermal reaction in step S2 is 120-180°C and the time is 6-10 h.
2. The photocatalytic self-Fenton water treatment method according to claim 1, characterized in that: In step S1, the drying temperature is 50-80°C and the drying time is 8-12 h.
3. The photocatalytic self-Fenton water treatment method according to claim 1, characterized in that: In step S2, the mass ratio of nitrogen carbonization to 4-carboxyphenylboric acid is 1:1.1-1:1.
6.
4. The photocatalytic self-Fenton water treatment method according to claim 1, characterized in that: The volume ratio of ethanol to water in step S2 is 1:4-1:
1.
5. The photocatalytic self-Fenton water treatment method according to claim 1, characterized in that: Fe 2+ The mass ratio of the CN-CPBA catalyst is 1:20-1:
5.
6. The photocatalytic self-Fenton water treatment method according to claim 1, characterized in that: The wavelength range of the light source is 200-1300 nm.
7. The photocatalytic self-Fenton water treatment method according to any one of claims 1 to 6, characterized in that: Used to degrade one or more of 4-chlorophenol, 2,4-dichlorophenol, bisphenol A, tetracycline, hydroquinone, resorcinol, and ciprofloxacin.
Citation Information
Patent Citations
Nanometer magnetic affinity material for efficiently capturing and losslessly releasing circulating tumor cells
CN114958748A